APLIKASI SMS GATEWAY MONITORING ORDER PASANG BARU DI UNIT ENTERPRISE PT TELKOM MALANG - Yulian, Winda (DINAMIKA DOTCOM, 2013)
The more work order existing Enterprise Unit PT Telkom Malang make admin increasingly overwhelmed serve customers and the Account Manager ( AM ) . Often the work order given to admin accumulate because sometimes there are other requests of any AM or customers . Such as billing information , disruption in customer service or customer data requests by PM.By admin is busy , sometimes another demand often exceeded AM . This makes work order information received by the AM is not realtime , thus hindering the course of work order . Given these problems , it is necessary to design a system that can access the status and position pairs of new orders through SMS service.SMS -based system that uses the mobile phone media is meant to be able to simplify , speed up while lowering the cost of doing accessing order information required by the PM to be given to the relevant unit . The results of this study are expected to be PM can get information about the status and position order more easily.Â Key Words : sms gateway, gammu, work order, Account Manager (AM)